Passive exposure and perceptions of smoke-free policies in hospital and university campuses among nursing students: A cross-sectional multicenter study - Marcela Fu; Yolanda Castellano; Kenza Laroussy; Antoni Baena; Mercè Margalef; Ariadna Feliu; Jordi Galimany-Masclans; Montse Puig-Llobet; Carmen Moreno-Arroyo; Raül Sancho; Albert Bueno; Antonio López; et al. (Tobacco Induced Diseases)
Introduction Outdoor smoke-free regulations reduce exposure to secondhand smoke (SHS) and help to denormalize tobacco use. As future key agents in health promotion, nursing students’ attitudes should agree with tobacco-control policies. The objectives of this study were: 1) assess nursing students’ exposure to SHS in nursing schools, 2) explore their perceptions of compliance with the existing smoke-free regulations in acute-care hospitals; and 2) describe their support for indoor and outdoor smoking bans on hospital and university campuses.